The properties and origins of spiral structure across the galaxy population - Hart, Ross Edward (2018)
Spiral galaxies are the most numerous type of massive galaxy in the low-redshift Universe. There have been a number of mechanisms proposed for their origin, including global density waves and swing amplified arms growing around local density perturbations. In order to understand the origin of arms fully, one requires a detailed study of all types of spiral structure. This thesis examines the global properties of the spiral galaxy population in large, complete samples of low-redshift galaxies. We utilise data from Galaxy Zoo, which provides visual classifications for a flux-limited sample of Sloan Digital Sky Survey (SDSS) galaxies, complete for m_r <17.0.